2023
DOI: 10.1371/journal.pone.0278500
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping for component traits of drought tolerance in dry beans (Phaseolus vulgaris L.)

Abstract: Understanding the genetic basis of traits of economic importance under drought stressed and well-watered conditions is important in enhancing genetic gains in dry beans (Phaseolus vulgaris L.). This research aims to: (i) identify markers associated with agronomic and physiological traits for drought tolerance and (ii) identify drought-related putative candidate genes within the mapped genomic regions. An andean and middle-american diversity panel (AMDP) comprising of 185 genotypes was screened in the field und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…GWAS and QTL mapping strategies in common bean populations have identified a large number of genomic regions and gene candidates behind a series of morphological traits under drought stress; for example, Mendes and collaborators ( Valdisser et al., 2020 ) reported 18 QTLs and 35 genes associated to seed weight under drought conditions in the Mesoamerican gene pool. Another study in the Andean and middle-American gene-pools identified 68 SNPs that were significantly associated with key agronomic and physiological traits under drought stressed and well-watered conditions ( Mutari et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…GWAS and QTL mapping strategies in common bean populations have identified a large number of genomic regions and gene candidates behind a series of morphological traits under drought stress; for example, Mendes and collaborators ( Valdisser et al., 2020 ) reported 18 QTLs and 35 genes associated to seed weight under drought conditions in the Mesoamerican gene pool. Another study in the Andean and middle-American gene-pools identified 68 SNPs that were significantly associated with key agronomic and physiological traits under drought stressed and well-watered conditions ( Mutari et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%